2021
DOI: 10.1177/00472875211047273
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality in Destination Marketing: Telepresence, Social Presence, and Tourists’ Visit Intentions

Abstract: Destination marketing organizations (DMOs) have widely adopted virtual reality (VR) commercials to highlight attractions for potential tourists and encourage visitation. This study extends the stimulus-organism-response (SOR) model by incorporating telepresence and social presence as stimuli and elucidating these factors’ possible interplay in jointly shaping users’ cognition, affection, and (re)visit intentions. A 2 × 2 between-subjects experiment was conducted with a sample of 254 participants. Results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 80 publications
4
57
1
2
Order By: Relevance
“…The findings elucidated that telepresence significantly influences consumers' hedonic performance, utilitarian performance, and behavioural intention. Furthermore, Ying et al (2021) investigated telepresence in the tourism context and confirmed that telepresence embedded in VR commercials evokes the user's intention to visit. However, scarce studies investigated the direct impact of telepresence on consumers' impulse purchases, especially in the live streaming commerce realm.…”
Section: Telepresencementioning
confidence: 80%
“…The findings elucidated that telepresence significantly influences consumers' hedonic performance, utilitarian performance, and behavioural intention. Furthermore, Ying et al (2021) investigated telepresence in the tourism context and confirmed that telepresence embedded in VR commercials evokes the user's intention to visit. However, scarce studies investigated the direct impact of telepresence on consumers' impulse purchases, especially in the live streaming commerce realm.…”
Section: Telepresencementioning
confidence: 80%
“…Later, with the development of distance education and social networks, many scholars questioned the media attribute of social presence, believing that users’ perception of the nature of media is more important than the attribute of media itself ( Ming et al, 2021 ). Social telepresence is described as a kind of warm social interaction on the website, that is, the extent to which the media allows users to psychologically perceive the existence of others ( Ying et al, 2022 ). Unlike traditional online shopping, live shopping has the characteristics of high real-time, high interaction and communication synchronization.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Subsequent studies have shown that stimuli to the organism can alter people’s cognition and emotion, which can involuntarily result in changes in behavioral intentions. The stimulus-organism-response (SOR) analytical framework has been applied to various aspects of tourism literature like tourist decision-making behavior ( Slama and Tashchian, 1987 ; Yadav et al, 2021 ; Yang et al, 2022 ), tourists’ consumption behavior ( Ying et al, 2021 ; Huy et al, 2022 ), aesthetics of tourism landscape ( Jani and Han, 2015 ), and tourist experiences ( Ben Haobin et al, 2021 ; Shin and Jeong, 2022 ; Talwar et al, 2022 ), which contributes abundant knowledge to this literature. In association with the literature, the current study develops and tests an extended SOR model to predict potential tourists’ behavior in heritage tourism.…”
Section: Stimuli-organism-response Model and Attitude-behavior-contex...mentioning
confidence: 99%